PENDAMPINGAN PELIBATAN ORANG TUA DALAM PENINGKATAN MINAT BELAJAR ANAK PADA MASA KENORMALAN BARU DI DESA BANJARSARI, KABUPATEN PROBOLINGGO - Adi Sutrisno; Indra Tjahyadi; Hosnol Wafa; Sri Andayani; Sugeng Edy Mulyono; Nuril Hidayati; M. Zamroni (Universitas Pahlawan Tuanku Tambusai, 2023)
This community service aims to increase children's interest in learning through learning methods that involve parents and children in the new normal period. The urgency of carrying out this activity was due to the low interest in learning for children in various villages in the Kabupaten Probolinggo during the new normal period. This community service activity was carried out in Desa Banjarsari, Kabupaten Probolinggo, Jawa Timur. The method used in this activity is the tutorial and mentoring method which is carried out offline in Desa Banjarsari, Kabupaten Probolinggo, Jawa Timur. The result of this community service activity is the ability of parents as children's learning partners, and the formation of parent-child learning partnerships in Desa Banjarsari, Kabupaten Probolinggo, Jawa Timur. The Community Service Team for the English Study Program, Faculty of Letters and Philosophy, University of Panca Marga found two advantages, as follows: 1) the presence of parents who are concerned about the success of their children's education, and 2) an informal atmosphere is an option in training and mentoring parents in increasing children's learning interest in the new normal era. Keywords: mentoring, interest in learning, parents, children